The hatred of literature - Marx, William, 1966- (The Belknap Press of Harvard University Press, 2018)
For 2,500 years literature has been condemned in the name of authority, truth, morality and society. But in making explicit what a society expects from literature, anti-literary discourse paradoxically asserts the validity of what it wishes to deny. The threat to literature's continued existence, William Marx writes, is not hatred but indifference.--